MAJOR CONTRIBUTORY FACTORS IN THE INITIATION OF ROOT RESORPTION (Review article) - Syamsiah Syam; Aries Chandra T.; Muhammad Ruslin (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Root resorption is one of the complications that often occur as a result of trauma in the permanent dentition. Resorption may be frequently observed unexpectedly because asymptomatic. The anterior teeth are more affected by root resorption and therefore it is utmost importance for the patient from socio-economic and psychological standpoint, various treatments can be perform to avoid severe damage to the teeth. Purpose: to know the management trauma of the permanent teeth so as to prevent the occurrence of resorption. Case: This report of seven case; 2 cases resorption due to avulsion injury without endodontic treatment, 2 cases resorption due to inadequate endodontic treatment, 2 cases post traumatic injury treated by splint and endodontic treatment, and 1 case resorption due to inadequate final restoration and preformed splint and endodontic treatment. Discussion: Tooth resorption results from injuries to or irritation of the periodontal ligament and / or tooth pulp and the treatment goal is to remove or eleminate bacteria to allow healing in the periradicular space. Conclusion: Treatment is based on removal or reduction of the source of infection.